Effect of Sleep and Salivary Glucose on Gingivitis in Children. (November 2016) - Alqaderi, H.; Tavares, M.; Hartman, M.; Goodson, J.M.
It has been shown that inadequate sleep has deleterious effects on health by suppressing immunity and promoting inflammation. The aim of this study was to investigate the effect of sleep and salivary glucose levels on the development of gingivitis in a prospective longitudinal study of Kuwaiti children. Data were collected from 10-y-old children ( N = 6, 316) in 2012 and again in 2014. Children were approximately equally distributed from 138 elementary schools representing the 6 governorates of Kuwait. Calibrated examiners conducted oral examination, self-reported sleep evaluation interviews, anthropomorphic measurements, and unstimulated whole saliva sample collection. Salivary glucose levels were measured by a florescent glucose oxidase method; values of salivary glucose ≥1.13 mg/dL were defined as high glucose levels. A multilevel random intercept and slope analysis was conducted to determine the relationship between sleep duration and gingivitis on 3 levels: within schools, among children, and over time. The outcome was the progression of the extent of gingival inflammation in children over time. The main independent variables were the number of daily sleep hours and salivary glucose levels. Other explanatory variables and confounders assessed were governorate, dental caries and restorations, and obesity by waist circumference (adjusted for snacking and sex). Gingivitis increased over time in children who had shorter sleep duration ( P < 0.05). Salivary glucose levels >1.13 mg/dL predicted gingivitis ( P < 0.05). Children who had more decayed or filled teeth had more gingivitis ( P < 0.05). No significant association was found between gingivitis and obesity. The level of gingivitis was different among the 6 governorates of Kuwait. Additionally, there was a strong clustering effect of the observations within schools and among children across time. Longitudinal analysis of 6, 316 Kuwaiti children revealed that shorter sleep duration and higher salivary glucose levels were both associated with increased gingival inflammation.